IMPLEMENTASI PEMBELAJARAN INKUIRI ONLINE DENGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MATERI FAKTOR LAJU REAKSI - Tri Laksono, Muhamad Bagus; Novita, Dian (Universitas Islam Balitar, 2022)
The purpose of this research is to implement the implementation of online inquiry learning syntax and train students' critical thinking skills on the reaction rate factor material. The research method is observation and test with the type of research that is pre-experimental design using model one group pretest-posttest. The research subjects were 18 students of XI MIPA 5 at SMAN 1 Gedangan. This study uses a random sampling technique with data collection techniques namely observation data and test data. Analysis of research data was carried out quantitatively and statistically based on the instrument data of pretest-posttest test sheets and syntax implementation sheets. Statistical analysis with paired samples t-test with normality test as a prerequisite test. The results of the study were 1) The critical thinking skills of students increased as indicated by the value of Sig. (2-tailed) < 0.05 which indicates a difference significant in pretest-posttest scores 2) The implementation of online inquiry learning is indicated by a percentage of 94.44% in learning I and 97.22% in learning II, so it can be stated that students' critical thinking skills can be trained with an online inquiry learning model.